The privatization experience of Japan the case of the Japan national railways - Mangahas, Joel V. (1995)
It is the idea of financial gain that drives governments to establish income-generating institutions, more commonly known as government-owned or -controlled corporations. Privatization as a means of saving a bankrupt or losing entity has been espoused by the governments in order to save themselves from further financial losses. Also, privatization is used as a course of action to remedy the moribund financial situation of said entities into a profitable and income-generating venture by turning over the ownership and control from the government to the private sector which usually has more business acumen when it comes to the remunerative aspects of commercial enterprise. Presented here is the predicament of Japan National Railways. Also, discussed is some of its inherent problems which are by and large similar to the ones encountered by the comparable agencies concerned.
Keywords: Privatization; Privatization -- Japan; Privatization policies -- Japan; Japan Railway System